Lack of Change in Markers of Presynaptic Terminal Abundance Alongside Subtle Reductions in Markers of Presynaptic Terminal Plasticity in Prefrontal Cortex of Schizophrenia Patients - Fung, Samantha J.; Sivagnanasundaram, Sinthuja; Weickert, Cynthia Shannon (Biological psychiatry (1969), 2011)
Reduced synaptic connectivity in frontal cortex may contribute to schizophrenia symptoms. While altered messenger RNA (mRNA) and protein expression of various synaptic genes have been found, discrepancies between studies mean a generalizable synaptic pathology has not been identified. We determined if mRNAs encoding presynaptic proteins enriched in inhibitory (vesicular gamma-aminobutyric acid transporter [VGAT] and complexin 1) and/or excitatory (vesicular glutamate transporter 1 [VGluT1] and complexin 2) terminals are altered in the dorsolateral prefrontal cortex of subjects with schizophrenia ( n = 37 patients, n = 37 control subjects). We also measured mRNA expression of markers associated with synaptic plasticity/neurite outgrowth (growth associated protein 43 [GAP43] and neuronal navigators [NAVs] 1 and 2) and mRNAs of other synaptic-associated proteins previously implicated in schizophrenia: dysbindin and vesicle-associated membrane protein 1 (VAMP1) mRNAs using quantitative polymerase chain reaction. No significant changes in complexin 1, VGAT, complexin 2, VGluT1, dysbindin, NAV2, or VAMP1 mRNA expression were found; however, expression of mRNAs associated with plasticity/cytoskeletal modification (GAP43 and NAV1) was reduced in schizophrenia. Although dysbindin mRNA did not differ in schizophrenia compared with control subjects, dysbindin mRNA positively correlated with GAP43 and NAV1 in schizophrenia but not in control subjects, suggesting low levels of dysbindin may be linked to reduced plasticity in the disease state. No relationships between three dysbindin genetic polymorphisms previously associated with dysbindin mRNA levels were found. A reduction in the plasticity of synaptic terminals supports the hypothesis that their reduced modifiability may contribute to neuropathology and working memory deficits in schizophrenia.